Insulinoma-related Endogenous Hypoglycaemia with a Negative Fasting Test : A Case Report and Literature Review (2022)
We present the case of a patient with a history of symptomatic hypoglycaemic episodes and a negative 72-hour fasting test with histological confirmation of insulinoma. A literature review of hyperinsulinaemic hypoglycaemia with a negative fasting test was performed.